Разложить многочлен на множители: а) х^4 – 6х^ 3 + 13х ^2 - 12х + 4 б) х (y + z)^ 2 + y (z + x) ^2 +z (x+y)^ 2 - 4 x y z

Разложить многочлен на множители: а) х^4 – 6х^ 3 + 13х ^2 - 12х + 4 б) х (y + z)^ 2 + y (z + x) ^2 +z (x+y)^ 2 - 4 x y z
Гость
Ответ(ы) на вопрос:
Гость
Разложить многочлены на множители:  а) х^4 – 6х^ 3 + 13х ^2 - 12х + 4   х=1     1^4 – 6(1^ 3 )+ 13(1 ^2) - 12(1) + 4 =1-6+13-12+4=0 ⇒  х^4 – 6х^ 3 + 13х ^2 - 12х + 4=(х-1)(х^ 3 - 5х ^2 + 8х - 4) х=1  1^ 3 - 5(1 ^2) + 8(1) - 4=1-5+8-4=0  ⇒ х^4–6х^3+13х^2-12х+4=(х-1)(х^3-5х^2+8х-4)=(х-1)(х-1)(х^2-4х+4)=(х-1)²(х-2)²  ⇔ х^4–6х^3+13х^2-12х+4=(х-1)²(х-2)² б) х (y + z)^ 2 + y (z + x) ^2 +z (x+y)^ 2 - 4 x y z
Не нашли ответ?
Ответить на вопрос
Похожие вопросы